Cepharanthine Exerts Antioxidant and Anti-Inflammatory Effects in Lipopolysaccharide (LPS)-Induced Macrophages and DSS-Induced Colitis Mice - Guangxin Chen; Da Wen; Lin Shen; Yazhi Feng; Qiuhong Xiong; Ping Li; Zhonghua Zhao (Molecules, 2023)
Cepharanthine (CEP), a biscoclaurine alkaloid extracted from Stephania cepharantha Hayata, has been widely used for the treatment of various acute and chronic diseases, including leukopenia, and snake bites. Here, our objective was to investigate the anti-oxidative stress and anti-inflammatory response effects of CEP in lipopolysaccharide (LPS)-induced macrophages as well as dextran sulfate sodium (DSS)-induced colitis mice. Our findings demonstrated that supplementation with CEP effectively mitigates body weight loss and elevation of disease activity index (DAI), reduces the malondialdehyde (MDA) content to 2.45 nM/mL while increasing the reduced glutathione (GSH) content to 35.53 μg/mL, inhibits inflammatory response, and maintains proper intestinal epithelium tight junctions in DSS-induced wild type (WT) mice. However, it failed to provide protective effects in DSS-induced transcription factor nuclear factor erythroid 2-related factor 2 (NRF2) knockout (NRF2−/−) mice. GSH content decreased to 10.85 μg/106 cells following LPS treatment, whereas supplementation with CEP increased the GSH content to 12.26 μg/106 cells. Moreover, CEP effectively attenuated ROS production in LPS-induced macrophages. Additionally, CEP exhibited inhibitory effects on pro-inflammatory cytokines and mediators in LPS-induced macrophages. Furthermore, we observed that supplementation with CEP promoted the expression of NRF2/heme oxygenase 1 (HO-1)/NADPH quinone oxidoreductase-1 (NQO-1) as well as the phosphorylation of the adenosine monophosphate-activated protein kinase alpha 1 (AMPK-α1)/protein kinase B (AKT)/glycogen synthase kinase-3 beta (GSK-3β) signaling pathway in macrophages while inhibiting the phosphorylation of the extracellular signal-regulated kinase (ERK)/c-Jun N-terminal kinase (JNK), and nuclear factor-kappa B p65 (NF-κB p65) signaling pathway in LPS-induced macrophages. Although CEP did not demonstrate inhibitory effects on oxidative stress or promote the expression of HO-1/NQO-1, it effectively activated the phosphorylation of the AMPK-α1/AKT/GSK-3β signaling pathway which is an upstream regulator of NRF2 in LPS-induced primary peritoneal macrophages from NRF2−/− mice. In summary, our findings suggest that CEP exerts protective effects against oxidative stress and inflammatory response by activating the AMPK-α1/AKT/GSK-3β/NRF2 signaling pathway while concurrently inhibiting the activation of mitogen activated protein kinases (MAPKs) and the NF-κB p65 signaling pathway. These results not only elucidate the mechanisms underlying CEP’s protective effects on colon oxidative stress and inflammation but also provide evidence supporting NRF2 as a potential therapeutic target for IBD treatment.